2009
DOI: 10.1063/1.3274044
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties and atomic structure of La2/3Ca1/3MnO3–YBa2Cu3O7 heterointerfaces

Abstract: A heterostructure comprised of a 2.7 nm (7 unit-cell) thick layer of the metallic ferromagnet La 2/3 Ca 1/3 MnO 3 and two 50 nm thick layers of the high-temperature superconductor YBa 2 Cu 3 O 7 epitaxially grown on (100) SrTiO 3 by pulsed-laser deposition was characterized by magnetization measurements and sphericalaberration-corrected high-resolution transmission electron microscopy (HRTEM).The saturation magnetization is about half of that in bulk La 2/3 Ca 1/3 MnO 3. A massive reduction of the magnetizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…Since it is known that the Curie temperature is strongly reduced in thin LCMO layers deposited on STO substrates, 40 2-3 u.c. is a remarkable result; the soft LCMO layer in between two YBCO layers has a Curie temperature of T Curie ¼ 265 K which is close to the bulk value of 275 K. This is in agreement with our previous work, 38 where we found that a 7 u.c. thick LCMO layer in between (001)-YBCO layers had a T Curie ¼ 210 K. In all heterostructures used in the present study we find a ferromagnetic ordering temperature of LCMO higher than 200 K (see Table I).…”
Section: Resultssupporting
confidence: 82%
“…Since it is known that the Curie temperature is strongly reduced in thin LCMO layers deposited on STO substrates, 40 2-3 u.c. is a remarkable result; the soft LCMO layer in between two YBCO layers has a Curie temperature of T Curie ¼ 265 K which is close to the bulk value of 275 K. This is in agreement with our previous work, 38 where we found that a 7 u.c. thick LCMO layer in between (001)-YBCO layers had a T Curie ¼ 210 K. In all heterostructures used in the present study we find a ferromagnetic ordering temperature of LCMO higher than 200 K (see Table I).…”
Section: Resultssupporting
confidence: 82%
“…Various x-ray and neutron techniques have been used to study bilayer/trilayer/superlattice HTSC-manganite heterostructures, such as YBCO/LCMO (La 1−x Ca x MnO 3 ) and YBCO/LSMO. [15][16][17][18][19] These studies reveal (a) a strongly (but not totally) suppressed Mn ferromagnetic moment at the manganite side of the interface, and/or (b) a small ferromagnetic Cu moment developing on the HTSC side of the interface. This is consistent with the observation of a reduced saturation magnetization per manganite layer compared to the bulk value.…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, it could be shown by dedicated analytical TEM investigations that the interfacial stacking patterns are different for the YBCO-LCMO interface (YBCO-BaOCuO 2 -(La,Ca)O-MnO-LCMO and the LCMO-YBCO one (LCMO-(La,Ca)O-MnO-BaO-CuO-BaO-CuO 2 -YBCO) [114]. The consequences of the details of the microstructure on the macroscopic properties of the films are not explores yet, however, they might be of importance for the charge carrier transport across the interfaces The early work on these hybrid structures and superlattices composed of a high temperature superconductor (e.g.…”
Section: Early Experimentsmentioning
confidence: 99%